2021
DOI: 10.1177/1087054721997555
|View full text |Cite
|
Sign up to set email alerts
|

Is Screen Time Throughout Adolescence Related to ADHD? Findings from 1993 Pelotas (Brazil) Birth Cohort Study

Abstract: Objective: This study investigated the association between screen time in adolescence and Attention Deficit Disorder (ADHD) at 22 years old. Method: A sample of 2333 participants aged 11 years old without ADHD from the 1993 Pelotas Birth Cohort Study (Brazil) was followed up until the age of 22. Screen time variables included time spent in television, video game and computer at 11, 15, and 18 years old. ADHD was assessed at 22 years. Results: ADHD symptoms at 22 years was positively associated with television … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…There is also evidence from a study that investigated the frequency of digital media use in adolescents over 2 years and revealed higher frequency of digital media use was associated with higher level of ADHD symptoms [ 79 ]. While the results from our cross-sectional study do not indicate a direction to the association between meeting the 24-HMB guideline for screen time and reduced risk of bullying others, the literature suggests limiting the screen time may support social coping, and/or reduce exposure to stimulation that may cause hyper vigilance, stress or increased ADHD symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…There is also evidence from a study that investigated the frequency of digital media use in adolescents over 2 years and revealed higher frequency of digital media use was associated with higher level of ADHD symptoms [ 79 ]. While the results from our cross-sectional study do not indicate a direction to the association between meeting the 24-HMB guideline for screen time and reduced risk of bullying others, the literature suggests limiting the screen time may support social coping, and/or reduce exposure to stimulation that may cause hyper vigilance, stress or increased ADHD symptoms [ 28 ].…”
Section: Discussionmentioning
confidence: 79%
“…engagement in MVPA). For example, promotion of physical activity through exergaming could be a valuable intervention strategy to reach this cohort [ 82 ], while meeting 24-HMB guidelines for non-educational screen time [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, foram positivos para TDAH aqueles indivíduos que pontuaram para pelo menos cinco sintomas de desatenção e/ou hiperatividade/impulsividade, com início dos sintomas antes dos 12 anos de idade e, por fim, manifestação de sintomas em pelo menos dois ambientes diferentes, por exemplo, escola, casa, entre outros, causando prejuízo clinicamente significativo do funcionamento social, acadêmico ou ocupacional por pelo menos seis meses 18 . Essa estratégia tem sido utilizada em estudos prévios 20 , 21 .…”
Section: Métodosunclassified
“…Several longitudinal studies from the communication sciences literature appear to suggest a temporal relationship between media use and subsequent ADHD characteristics, although most studies in this field did not include groups with clinical ADHD diagnoses, and potential confounds of this work and the implications have been widely debated. In the domain of television consumption, a Brazilian cohort study with adolescents from the general population found that ADHD symptoms at age 22 were related to television time at age 11, and total screen time at age 18 [ 28 ]. Another study has shown that the frequency of watching television at age 14 is linked to attention problems at age 16 after controlling for prior family and cognitive factors [ 29 ].…”
Section: Adhd and (Social) Media Use: A Brief Literature Reviewmentioning
confidence: 99%